2017
DOI: 10.1590/1807-1929/agriambi.v21n12p822-827
|View full text |Cite
|
Sign up to set email alerts
|

Defoliation of sweet corn plants under irrigation depths and its impact on gas exchange

Abstract: A B S T R A C TThe objective of this work was to evaluate leaf gas exchanges of sweet corn as a function of defoliation when submitted to different irrigation depths. The experimental design was randomized blocks in split-plot scheme, with four irrigation depths in the plots [50, 75, 100 and 125% of crop evapotranspiration (ETc)], and three levels of defoliation in the subplots (0%, control; 35%, removal of four fully expanded leaves; 100%, total removal of the leaves -section of the aerial part) with three re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The highest IWUE of corn plants in the 2017/2 seasons, followed by the 2016/2 (Table 2), proved the efficiency in water use in periods of greater water deficit compared to the other seasons (Figure 1). Similar behavior has already been reported in other studies [27,28]. This effect may also be related to the greater development of the root system, obtained via the application of the biostimulant, given the presence of auxins, the main hormone involved in root growth [16,29,30].…”
Section: Discussionsupporting
confidence: 84%
“…The highest IWUE of corn plants in the 2017/2 seasons, followed by the 2016/2 (Table 2), proved the efficiency in water use in periods of greater water deficit compared to the other seasons (Figure 1). Similar behavior has already been reported in other studies [27,28]. This effect may also be related to the greater development of the root system, obtained via the application of the biostimulant, given the presence of auxins, the main hormone involved in root growth [16,29,30].…”
Section: Discussionsupporting
confidence: 84%
“…They concluded that regional water management strategies could be effective in buffering against the interannual climate variability of recharge, while localized management strategies could increase irrigation efficiency by targeting crop and soil texture drivers. Water deficits reduce leaf area but can be compensated with irrigation [60]. These authors found that plants counteract leaf stress by activating a mechanism of photosynthetic compensation.…”
Section: Droughtmentioning
confidence: 99%
“…Such facts interfere with the availability of chemical energy (ATP) from photosynthesis, which is produced only in cells containing chlorophyll in the presence of light (Ibrahim et al, 2010;Addai & Ghanney, 2018;Lima-Primo et al, 2019). Reduction of leaf area interferes with photosynthesis and, consequently, with hormonal equilibrium, index of chlorophylls, stomatic resistance, and ATP production (Ibrahim et al, 2010;Santos et al, 2017;Addai & Ghanney, 2018), resulting in a production decline (Figures 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
“…During its cycle, cowpea is challenged by defoliating herbivorous insects. Such insects reduce the leaf area and photosynthetic capacity of the plant, promoting significant production losses (Ibrahim et al, 2010;Santos et al, 2017;Smiderle et al, 2017;Addai & Ghanney, 2018;Lima-Primo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%